Valuation of compounded deferred tax assets for the banking sector, using the binomial CRR algorithm - João Marques Silva (Taylor & Francis Group, 2019)
Deferred tax asset (DTA) is a tax/accounting concept that refers to an asset that may be used to reduce future tax liabilities of the holder. In the banking sector, it usually refers to situations where a bank has either overpaid taxes, paid taxes in advance or has carry-over of losses (the latter being the most common situation). In fact, accounting and tax losses may be used to shield future profits from taxation, through tax loss carry-forwards. In other words, DTAs are contingent claims, whose underlying assets are banks future profits. Consequently, the correct approach to value such rights implies necessarily, the use of a contingent claims valuation framework. Despite that, one common practice consists in valuing DTAs as though they would be used at 100% without even discounting for the time value of money. Another common procedure consists in considering a subjective “valuation allowance”, valuing the deferred tax asset as a certain percentage of the corresponding maximum value, according to future expectations on the company’s financial performance. The purpose of this paper is exactly to propose a precise and conceptually sound approach to value DTAs. For that purpose, making use of an adapted binomial CRR (Cox, Ross and Rubinstein) algorithm, we derive a precise way to value DTAs. This way, the DTAs are valued in a similar way of the Binomial Options Pricing Model, and the subjectivity of its evaluation is greatly reduced. We will see that with the proposed evaluation techniques, the DTA’s expected value will be much lower than the values normally used in today’s practice, and the bank’s financial analysis will lead to much more sound and realistic results.